2021
DOI: 10.3390/diagnostics11091681
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Advanced NSCLC: [18F]FDG PET/CT as a Troubleshooter in Treatment Response

Abstract: Introduction: The aim of this study was to investigate whether [18F]FDG PET/CT-derived semi-quantitative parameters can predict immunotherapy treatment response in non-small cell lung cancer (NSCLC) patients. Secondly, immune-related adverse events (irAEs) and lymphoid cell-rich organs activation were evaluated. Materials and Methods: Twenty-eight patients who underwent [18F]FDG PET/CT scans before and at first restaging therapy with immuno-checkpoint inhibitors (ICIs) were retrospectively analyzed. PET-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…All of them classified responses to ICIs as complete remission (CR), partial response (PR), stable disease (SD), and progression of disease (PD) based on the Response Evaluation Criteria In Solid Tumors (RECIST) 1.1. Four articles demonstrated that none of the PET/CT parameters significantly correlated with ICIs response ( 17 , 23 , 28 , 29 ). However, the other four studies showed that NSCLC patients who achieved CR, PR, or SD after ICIs treatment had significantly lower median MTV values than those with PD ( 16 , 26 , 27 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of them classified responses to ICIs as complete remission (CR), partial response (PR), stable disease (SD), and progression of disease (PD) based on the Response Evaluation Criteria In Solid Tumors (RECIST) 1.1. Four articles demonstrated that none of the PET/CT parameters significantly correlated with ICIs response ( 17 , 23 , 28 , 29 ). However, the other four studies showed that NSCLC patients who achieved CR, PR, or SD after ICIs treatment had significantly lower median MTV values than those with PD ( 16 , 26 , 27 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies assessed the objective response based on RECIST 1.1. Four studies showed NSCLC patients who achieved CR, PR, or SD after ICIs treatment had significantly lower median MTV values than those with PD ( 16 , 26 , 27 , 30 ), while four demonstrated no significant correlation ( 17 , 23 , 28 , 29 ). More studies with consistent response assessments are needed to determine whether MTV is associated with the objective response of ICIs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, several studies investigated the pre-therapeutic standardized uptake value (SUV) of non-tumorous lung tissue in [ 18 F]-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) as a potential predictive biomarker for the risk of developing radiation therapy-associated and immune checkpoint inhibitor associated pneumonitis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In individuals undergoing radiation therapy, a significant partial correlation exists between an increased pre-radiotherapeutic PET-measured glucose uptake and an elevated risk of radiation-induced pneumonitis [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In individuals undergoing radiation therapy, a significant partial correlation exists between an increased pre-radiotherapeutic PET-measured glucose uptake and an elevated risk of radiation-induced pneumonitis [ 12 , 15 ]. However, most studies focusing on the predictability of immunotherapy-associated pneumonitis failed to establish a significant correlation between pre-therapeutic FDG uptake and the risk of therapy-related pneumonitis [ 16 , 17 , 18 , 19 , 20 , 21 ]. In the studies referenced, the impact of patients’ comorbidities on the SUV was not incorporated into the analyses.…”
Section: Introductionmentioning
confidence: 99%